Ukrainian Interior Troops officer general culture and the ways of its development - Moldavchuk, V. S. (Honor and Law, 2019)
The essence of the notion of the Ukrainian officer general culture has been researched and the ways of its development has been introduced. The issue concerning the influence of the Interior Troops officer general culture on the institutional image formation has been worked out.